2021
DOI: 10.1029/2021jb021839
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of Himalayan Leucogranites: Perspective From a Combined Elemental and Fe‐Sr‐Nd Isotope Study

Abstract: The petrogenesis of Himalayan leucogranites remains crucial for understanding the thermal and tectonic evolution of the Himalayan orogen. To understand whether they are largely pristine melts of crustal anatexis or have experienced a high degree of fractional crystallization (FC), we present Fe isotopic data of 30 representative Himalayan leucogranites and 9 local metasedimentary rocks. Excepting three garnet leucogranites with low δ 56 Fe (−0.04‰-0.06‰) that are likely affected by garnet accumulation, tourmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 128 publications
1
1
0
Order By: Relevance
“…The Gyirong leucogranite shows high ( 87 Sr/ 86 Sr) i ratios (0.7548-7586), high Rb contents, and low Sr and Ba contents (Gao et al, 2017;Wang et al, 2017), which can be ascribed to fluid-absent melting of muscovite in metasedimentary sources. This interpretation is also supported by recent Mg-Fe-Sr-Nd isotope studies (e.g., Tian et al, 2020;Shi et al, 2021). Note that some authors found that the Himalayan leucogranites do not record any mantle material contribution to the sources (Inger and Harris, 1993;opkinson et al, 2017).…”
Section: Boron Isotope Variation and Genetic Implicationssupporting
confidence: 59%
“…The Gyirong leucogranite shows high ( 87 Sr/ 86 Sr) i ratios (0.7548-7586), high Rb contents, and low Sr and Ba contents (Gao et al, 2017;Wang et al, 2017), which can be ascribed to fluid-absent melting of muscovite in metasedimentary sources. This interpretation is also supported by recent Mg-Fe-Sr-Nd isotope studies (e.g., Tian et al, 2020;Shi et al, 2021). Note that some authors found that the Himalayan leucogranites do not record any mantle material contribution to the sources (Inger and Harris, 1993;opkinson et al, 2017).…”
Section: Boron Isotope Variation and Genetic Implicationssupporting
confidence: 59%
“…Here we report elemental and Mg isotopic data of 9 Himalayan carbonate‐free metasedimentary rocks and 23 Himalayan carbonate‐bearing metasedimentary rocks which were collected from Bhutan and Nepal Himalaya (Groppo et al., 2021; Rolfo et al., 2017; Shi et al., 2021; Table S1 in Supporting Information ), to establish the correlation between bulk Mg isotopic compositions and ICAs. In order to reveal the elemental and isotopic characteristics of the present carbonates and silicate components in the carbonate‐bearing rocks, five samples were selected to conduct leaching experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the geochemical compositions of anatectic melts cannot unequivocally discriminate dehydration versus water‐fluxed melting and low‐degree partial melting versus fractional crystallization (Bartoli, 2021; Guo & Wilson, 2012). Recent studies have suggested that a number of stable isotope systems are useful in tracing the sources and petrogenetic processes of anatectic granites, which complement traditional geochemical approaches (Fan et al., 2021; Shi et al., 2021; Wang, Zhang, et al., 2020; Wang, Hao, et al., 2020). The stable B and Mo isotope systems have been used to study mantle heterogeneity and fluid or melt recycling during subduction‐related processes (Chen et al., 2022; Freymuth et al., 2015; König et al., 2016; Li et al., 2021).…”
Section: Introductionmentioning
confidence: 99%